Generations of Universities: Features of Cultivated Thinking Types. What Will the Thinking be Like in University 4.0? - V. S. Efimov; A. V. Lapteva (Высшее образование в России)
The university is considered in historical retrospect and perspective as a cognitive institution of society that ensures the reproduction and development of thinking. The concept of “university generation” is basic for the study. Three generations of universities are distinguished in history (scholastic, research, entrepreneurial); the university of the future is considered as a fourthgeneration university (“cognitive university”).Universities of definite generations developed specific historical types of thinking. It is proposed to define types of thinking through their characteristic “objects”, “methods” and “intentions”. The peculiarity of the university as a cognitive institution is that it works at the level of foundations – it creates and reproduces the foundations of worldviews and social practices. These can be ontological, value-based, socio-practical, anthropological foundations of knowledge systems and practices.A hypothesis is proposed: the fourth generation university will cultivate methodological thinking (“thinking about thinking”), its key objective will be the formation of collective and hybrid (including AI) intelligences, and the development of technologies for their work. The activities of University 4.0 will be aimed at creating the foundations of new practices (ontological, value-based, ethical, anthropological) and setting precedents for these practices.